KEBIJAKAN CHINA PASKA PERANG DAGANG, PANDEMIK DAN ANTISIPASI MENGHADAPI RESESI DUNIA TAHUN 2023 - Hasibuan, Febri Dirgantara; Nuraini, Azzahra Egidia; Putra, Rama Maulana; Nur Fitriani, Anna Tasya; Sudrajat, Andhiene Kartika (Emerald: Journal of Economics and Social Sciences, 2023)
The increasing tension in trade relations between China and America has forced China to take steps to maintain the stability of China's economy, especially since China's economy has just recovered from the Covid-19 pandemic. Therefore, in facing the 2023 economic crisis, China has prepared policies to achieve its national interests, especially in the economic aspect. In analyzing China's foreign policy to deal with the 2023 economic problems, the foreign policy, and national interest concept is used as an approach from the perspective of Neoclassical Realism. The qualitative method is used, where data are collected through library research, by taking various sources and references to support this research. Data collection techniques are through listening and recording important information in conducting data analysis through data reduction. The findings in this paper are to push forward the BRI program and BRICS activation through geoeconomic strategy